GaAs IC Symposium IEEE Gallium Arsenide Integrated Circuit Symposium. 18th Annual Technical Digest 1996
DOI: 10.1109/gaas.1996.567635
|View full text |Cite
|
Sign up to set email alerts
|

Slip defect generation on GaAs wafers during high temperature process: a thermoelastic study from a crystallographic viewpoint

Abstract: In this work we investigate the mechanism of slip defect generation, using a simple heat flow simulation during an MBE process, a wafer heating apparatus, and a thermoelastic analysis from a crystallographic viewpoint. We find that the slip defect pattern predicted from the analysis agrees with the experiment and confirm that slip defects are prone to occur at orientation flat (OF) and notch edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Fig. 2 shows in good agreement to the experimental results [1][2][3][4][5][6][7][8][9] that the area where minority type dislocations can exist ranges from about 10°to about 35°around 110 peripheral areas. Our model does not give an explanation for the frequently observed predominance of minority type dislocation bundles at the major flat, but this is to be expected from our assumption of a perfectly circular wafer.…”
Section: Model For Thermal Treatment Induced Plastic Deformation In Csupporting
confidence: 78%
See 2 more Smart Citations
“…Fig. 2 shows in good agreement to the experimental results [1][2][3][4][5][6][7][8][9] that the area where minority type dislocations can exist ranges from about 10°to about 35°around 110 peripheral areas. Our model does not give an explanation for the frequently observed predominance of minority type dislocation bundles at the major flat, but this is to be expected from our assumption of a perfectly circular wafer.…”
Section: Model For Thermal Treatment Induced Plastic Deformation In Csupporting
confidence: 78%
“…The models given in [1,2,9] describe the frequently occurring predominance of minority type dislocation bundles at the area of the major flat reasonably well, but are not applicable to majority type dislocation bundles since they predict a spatial distribution with an eightfold symmetry. Applying Curie's well-known symmetry principle [10,11], we found that the symmetry of this set is the point group 4( 2m [6], which does not contain an eight-fold symmetry axis.…”
Section: Main Experimental Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The X‐ray transmission analysis showed that this phenomenon has nothing to do with lattice misfit but solely with thermal treatment induced plastic deformation . Even temperature inhomogeneities across the area of the substrate holder are responsible for the formation of such slip lines . It is assumed that the nucleation of majority‐type dislocation bundles took place as half‐loops at surface irregularities at the wafer edge.…”
Section: Experimental Observations and Counter Actionsmentioning
confidence: 99%